ChemInform Abstract: Carbohydrate‐Based Phosphines as Supporting Ligand for Palladium‐Catalyzed Suzuki—Miyaura Cross‐Coupling Reaction. Issue 44 (4th November 2014) - Shi, Ji‐cheng; Zhou, Zhonggao; Zheng, Shan; Zhang, Qing; Jia, Li; Lin, Jinhuo
Abstract The title ligand in combination with Pd(II) is found to be highly effective for the Suzuki‐Miyaura reaction of aryl bromides and activated aryl chlorides.